Seizures and epilepsy of autoimmune origin: A long-term prospective study. (October 2020) - Falip, Mercè; Jaraba, Sònia; Rodríguez-Bel, Laura; Castañer, Sara; Mora, Jaume; Arroyo, Pablo; Miro, Júlia; Sala-Padró, Jacint; Martínez-Yélamos, Sergio; Casasnovas, Carlos; Gascon-Bayarri, Jordi; Real, Eva; et al.
Highlights: Acute symptomatic seizures secondary to autoimmune encephalitis, or autoimmune-related epilepsy, represent an uncommon entity. Apart from some specific seizure types and EEG patterns, the only diagnostic clues are antineuronal and onconeuronal antibodies. Response to immunotherapy may be highly sensitive but not specific. More than one third of patients who suffer acute symptomatic seizures secondary to autoimmune encephalitis develop epilepsy over time. Patients with epilepsy + GAD ab and epilepsy in systemic autoimmune diseases were the most frequent subgroups of autoimmune-related epilepsy. Abstract: Objective: To follow prospectively a group of patients with seizures or epilepsy and suggestive clinical features of autoimmune aetiology and find out how many are finally diagnosed with acute symptomatic seizures (ASS) secondary to autoimmune encephalitis or autoimmune-related epilepsy, and how many develop epilepsy. Methods: Consecutive patients meeting the inclusion criteria from 2010 to 2018 were identified. Patients were classified as confirmed, probable autoimmune, non-autoimmune, or unknown. Results: One-hundred and nine patients were included, 64 (48.7 %) women, mean age 55.2 years (SD 17.9). ASS were reported by 61 patients (56 %), while 48 presented epilepsy (44 %). During follow-up 18 patients died (16.5 %). Final diagnosis was autoimmune-relatedepilepsy (confirmed + probable) in 22 cases and ASS secondary to autoimmune encephalitis (confirmed or probable) in 27, non-autoimmune aetiologies or other diagnosis in 49 (44 %), and unknown aetiology in 11 (10.2 %). Neuronal antibodies (ab) were found in 27 patients (24.7 %). T-lymphocyte infiltration in temporal lobes was observed in 2/8 patients (20 %). Neuronal ab were more frequent in the autoimmune groups: 17 patients (29.8 %) vs 1(2.3 %), p:0.001, and they suffered more autoimmune diseases: 37 (75.5 %) vs 12 (24.48 %), p:0.0001, and 34 (69 %) vs 22 (44.9 %) p:0.027, respectively. All patients with GAD ab 17/17 (100 %) evolved to chronic disease. Four patients (29 %) with ASS secondary to autoimmune encephalitis developed epilepsy. Significance: ASS secondary to autoimmune encephalitis or autoimmune-related epilepsy will be diagnosed in nearly half of patients who have been suspected of it. The only diagnostic clue is neuronal ab. Patients who have suffered ASS secondary to autoimmune encephalitis may develop epilepsy over time.